2018
DOI: 10.1111/1346-8138.14502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic urticaria on quality of life and work in Japan: Results of a real‐world study

Abstract: Little attention has been given to the burden of chronic urticaria (CU) in Japan compared with other skin diseases, such as atopic dermatitis (AD) and psoriasis. The primary objective of the RELEASE study was to evaluate the real‐life quality‐of‐life impairment in CU patients in Japan. Data were collected from 1443 urticaria, 1668 AD and 435 psoriatic patients; 552 urticaria patients who presented urticaria symptoms for over 6 weeks were defined as CU. The mean Dermatology Life Quality Index (DLQI) total score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
71
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 28 publications
13
71
1
2
Order By: Relevance
“…Similar to our study, the Italian study found patients experienced a range of negative emotions, with frustration common in the period leading to diagnosis and a high proportion of patients reporting impairment to QoL (11). Other studies have also reported patient dissatisfaction with their treatment and physicians (5,8). However, patients whose physicians had discussed the emotional impact of CSU were significantly (p < 0.001) more satisfied with treatment and more trusting of their physician.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to our study, the Italian study found patients experienced a range of negative emotions, with frustration common in the period leading to diagnosis and a high proportion of patients reporting impairment to QoL (11). Other studies have also reported patient dissatisfaction with their treatment and physicians (5,8). However, patients whose physicians had discussed the emotional impact of CSU were significantly (p < 0.001) more satisfied with treatment and more trusting of their physician.…”
Section: Discussionsupporting
confidence: 86%
“…The extent to which patients' quality of life (QoL) can be affected by CSU has been demonstrated in numerous studies (1,2,(4)(5)(6)(7)(8) and goes beyond effects on skin (e.g. itching), with many patients reporting fatigue, pain, and sleep disturbances.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent development of biologics, such as omalizumab, humanized monoclonal antibody against IgE, have largely improved its treatment [38,39]. However, many patients still do not benefit from or tolerate such therapies, and the molecular mechanism of wheal formation in urticaria is poorly understood [1,2,5]. It is largely due to a lack of proper experimental, small animal models for urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria is classified as the chronic type when it lasts for 6 weeks or longer, and is further divided into chronic spontaneous urticaria (CSU) and chronic inducible urticaria [3,4]. Chronic urticaria has a significant impact on quality-of-life due to regular recurrence of disfiguring eruptions with itching, and unknown etiology [1,5]. Moreover, urticaria may be a symptom of anaphylaxis that seriously affects the patient's life.…”
Section: Introductionmentioning
confidence: 99%